The Effect of Exercise Training on Gait, Balance, and Physical Fitness Asymmetries in Persons With Chronic Neurological Conditions: A Systematic Review of Randomized Controlled Trials - Farrell, John W.; Merkas, Jordan; Pilutti, Lara A. (Frontiers in Physiology, 2020)
Background: Persons with chronic neurological conditions (CNCs) often present with asymmetrical impairments, creating significant differences between contralateral limbs in body functions. These asymmetries have been associated with reduced mobility and balance, and are often targeted for reduction during rehabilitation. Exercise training has established benefits for persons with CNCs, and may have positive effects on asymmetry outcomes. Objectives: The purpose of this review was to summarize the current evidence for the effects exercise training on gait, balance, and physical fitness asymmetry in randomized control trials (RCTs) of persons with CNCs. Methods: A search of four electronic databases (EMBASE, CINAHL, SPORTdiscus, and ovidMEDLINE) was conducted following the structured Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: The search retrieved 3,493 articles, with 465 articles assessed for eligibly, and nine articles meeting the criteria for inclusion. Of the included articles, five incorporated resistance exercise, three incorporated aerobic exercise, and one incorporated combined exercise (i.e., resistance and aerobic exercise). Gait asymmetry improved significantly in four studies after resistance, aerobic, and combined exercise. Significant improvements in weight bearing asymmetry were reported in three studies after resistance exercise. One study reported significant improvements in both gait and balance asymmetry after resistance exercise. Conclusions: Preliminary evidence suggests that exercise training, as a component of rehabilitation, may have positive effects on gait and balance asymmetry in persons with CNCs. Several limitations of the current literature were noted, including a limited number of studies, combination of exercise with other rehabilitation modalities, a lack of reporting on exercise prescriptions (e.g., number of repetitions, intensity), and variability in the calculation of asymmetry outcomes. These limitations prevent definitive conclusions on the effects of exercise training on asymmetry outcomes. Future trials are needed to determine the potential of exercise training for reducing asymmetry in persons with CNCs.